2021
DOI: 10.3390/electronics10060750
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Uta-Karuta: Development and Evaluation of an Accessible Card Game System Using Audible Cards for the Visually Impaired

Abstract: Playing board games is important for people with a visually impairment, as it promotes interactive socialization and communication skills. However, some board games are not accessible to them at present. In this study, we proposed an auditory card game system that presents a card’s contents with auditory stimuli to all players, towards playing equally with others, regardless of whether they have a visual impairment or not as one of the solutions to make board games accessible. This proposal contributes signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Various studies have shown that people who are visually impaired show higher levels of auditory ability due to their frequent use in this population. These abilities are pertinent to auditory skills such as echo processing, voice localizing, and distance estimation [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that people who are visually impaired show higher levels of auditory ability due to their frequent use in this population. These abilities are pertinent to auditory skills such as echo processing, voice localizing, and distance estimation [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some board games are not accessible to them at present. In [6], Miyakawa et al proposed an auditory card game system that presents a card's contents with auditory stimuli to all players, geared toward playing equally with others regardless of whether they have a visual impairment or not, as one of the solutions to make board games accessible. This proposal contributes significantly to expanding the range of inclusive board games for the visually impaired.…”
Section: Introductionmentioning
confidence: 99%